The Role of Economic Freedom in Integrating Developing Asian Countries into Global Value Chains - Cavin Dennis Tito Siregar; Estro Dariatno Sihaloho; Harsa Pratama Syarief; Wiksa Dana (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The world economy is increasingly more globalized and Global Value Chains (GVCs) played a greater role in international trade and production which provides opportunities for economic growth and development. This paper examines the linkages between economic freedom and Global Value Chains. The developing nations in Asia need to have the ability to integrate themselves in GVCs in order to gain access to higher-value activities in GVCs. The objective of this study is to see the impact of the Economic Freedom Index, Female Labor Force Participation Rate and the Global Competitiveness Index (GCI) in Asian countries considered as developing economies by the IMF on the countries’ position in GVCs measured using value-added indicators. The presence of the Global Competitiveness Index (GCI) variable can indicate the role of government, consistency of policies, infrastructure and institutional formation, which is correlated in the level of Economic Freedom of developing nations.  This paper uses the Data Panel regression model consisting of multiple indicators of all the variables used from 25 developing countries in Asia from 2009 to 2017. Analysis indicates that the variables have an overall positive relationship with the level of integration of the countries into GVCs.